2017
DOI: 10.1155/2017/5741821
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytes in Mucoepidermoid Carcinoma of the Palate: Diagnostic Challenges

Abstract: The origin of a salivary gland tumour is attributed to cells at various levels of differentiation which present histologically as diverse tissues and cellular patterns. Mitochondria-rich, eosinophilic oncocytes are cells commonly encountered in salivary gland neoplasms. We report a case of mucoepidermoid carcinoma (MEC) in the palate of a 43-year-old female that exhibited a prominent oncocytic component. While the parotid and submandibular glands have been reported as predominant sites for oncocytic MEC (OMEC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…MEC is composed of epidermoid, mucous and intermediate cells in varying proportions and may also have other cell types such as clear cells, columnar cells, goblet cells, and oncocytes 9 . Variants of MEC include sebaceous, clear, spindle, melanocytic, goblet, sclerosing, psammomatous, unicystic, and oncocytic 10‐12 . Extensive oncocytic change in MEC of the parotid gland was first reported by Sidhu and Waldo 13 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…MEC is composed of epidermoid, mucous and intermediate cells in varying proportions and may also have other cell types such as clear cells, columnar cells, goblet cells, and oncocytes 9 . Variants of MEC include sebaceous, clear, spindle, melanocytic, goblet, sclerosing, psammomatous, unicystic, and oncocytic 10‐12 . Extensive oncocytic change in MEC of the parotid gland was first reported by Sidhu and Waldo 13 .…”
Section: Discussionmentioning
confidence: 95%
“…It is not established whether oncocytic differentiation has any prognostic role 11,12,14 . Oncocytic variant of MEC poses a diagnostic challenge on cytology as oncocytes can be seen in metaplasia or age‐related degeneration, oncocytic hyperplasia, benign tumours like oncocytoma, Warthin's tumour, and malignant lesions like oncocytic carcinoma, or oncocytic variant of other salivary gland tumours 10,15,16 . Wade et al 4 reported the presence of oncocytes in 22% cases of MEC on cytology and lymphocytes in 78% cases.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 T h e m aj o r i t y o f t h e muc o e pid e r m oid carcinomas, anatomically, occur at the junction between the hard/soft palate and deep surface of the tumor, usually supported by the hard palate bone. 5 The ultimate management of the inner bone margin of such tumors has not been conclusively established yet, but the treatment by partial maxillectomy or palatal fenestration are indicated for large and bulky tumors or those with radiological and tomographic evidence of bone erosion or invasion. [2][3][4][5][6] The use of three-dimensional principles has facilitated the observation and comparison of several treatment plannings.…”
Section: Introductionmentioning
confidence: 99%
“…5 The ultimate management of the inner bone margin of such tumors has not been conclusively established yet, but the treatment by partial maxillectomy or palatal fenestration are indicated for large and bulky tumors or those with radiological and tomographic evidence of bone erosion or invasion. [2][3][4][5][6] The use of three-dimensional principles has facilitated the observation and comparison of several treatment plannings. 7 The performance of a volumetric evaluation of the overall morphological changes in noble structures, thus enabling a better understanding of the tumor's morphology and its proximity to adjacent tissues is allowed by three-dimensional reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…PALABRAS CLAVE: glándulas salivales; oncocitos; oncocitoma; hiperplasia oncocítica adenomatosa multinodular; histología; inmunohistoquímica. Mandel & Carrao (2005) describen al oncocito como una célula que se origina probablemente a partir de la transformación metaplásica del epitelio ductal trario, estudios ultraestructurales indican que los oncocitos salivales se originarían como consecuencia de una hiperplasia celular adaptativa compensatoria por una mutación somática (Zagólski et al, 2006;Kumar et al, 2017).…”
Section: Introductionunclassified